2009
DOI: 10.1038/hr.2008.19
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits insulin-like growth factor-1-induced cell migration by the suppression of extracellular signal-regulated kinase 1/2 activation, but not Akt in vascular smooth muscle cells

Abstract: Adiponectin, an adipocyte-derived hormone, has been proposed to show antiatherogenic properties through the inhibitory effects against various growth factors. Insulin-like growth factor-1 (IGF-1) is one of the potent mitogens, which has been considered to play important roles in both atherogenesis and plaque stabilization in accordance to the phase of atherosclerosis. The aim of this study is to elucidate the adiponectin effects on IGF-1-induced cell migration and its intracellular signaling pathways in vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 31 publications
1
41
1
Order By: Relevance
“…For example, activation of AMPK by adiponectin inhibits lipopolysaccharide-induced adventitial fibroblast migration (44), and insulin-like growth factor-1-induced vascular smooth muscle cell migration is also suppressed by AMPK activation (45). However, AMPK stimulates human umbilical vein endothelium cell migration (46) and induces transendothelial lymphocyte migration by endothelial nitric-oxide synthase activation (47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of AMPK by adiponectin inhibits lipopolysaccharide-induced adventitial fibroblast migration (44), and insulin-like growth factor-1-induced vascular smooth muscle cell migration is also suppressed by AMPK activation (45). However, AMPK stimulates human umbilical vein endothelium cell migration (46) and induces transendothelial lymphocyte migration by endothelial nitric-oxide synthase activation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin inhibits PDGF-induced RMC migration (Zhan et al 2003, Yamaguchi et al 2004. We have already demonstrated that adiponectin inhibited IGF-1-induced cell migration through suppression of ERK1/2 activation, which might be implicated in AMPK activation in VSMCs (Motobayashi et al 2009). However, detailed mechanisms including signaling crosstalk have not yet been studied in RMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines have become widely accepted as key regulators of VSMC proliferation and viability, two important cellular processes in atherogenesis [16][17][18] . Most research so far has focused on the direct roles of those substances in VSMC physiology; however, the physiological regulation and role of HFD in mediating the unhealthy effects of adipocytes on VSMC have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct vascular consequences, adipokines may regulate VSMC proliferation, migration and viability. Leptin causes VSMC proliferation and hypertrophy and adiponectin inhibits VSMC migration and promotes their differentiation [16][17][18] . Most research so far has focused on the direct roles of those substances on VSMC physiology without considering the direct impact of adipocytes.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%